Agama dan Tantangan Sains Modern - Amsal Bakhtiar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
Before discussing the role and challenges of religion in the era of science and technology, it is essential to examine the historical relationship between religion and science in human civilization. The evolution of human civilization has been shaped by the interplay of various values, including those of science and religion. Throughout history, new scientific discoveries have often sparked social upheaval, as societies struggle to reconcile novel findings with existing beliefs. This paper explores key historical moments of tension and adaptation between religion and science, from Greek philosophy and the Islamic Golden Age to the Renaissance and modern secularism. While scientific advancements have led to a secular worldview in the West, a resurgence of spirituality and religious movements is observed in contemporary times. The paper further discusses the potential for reconciliation between religion and science in the modern world.